The Impact of Suspect Race and Precipitating Incident on Community Members’ Assessments of Deadly Force Reasonableness - Fridell, Lorie A. (Homicide studies, 2023)
The contrast between many community members’ views about the extent to which force used by police is excessive and the criminal justice system’s determination of same suggests a “reasonableness divide.” Using survey data from 3,600 nationally representative adults, this study assessed one possible reason for this divide—that community members evaluate the reasonableness of deadly force using factors that are not considered in legal assessments. The results affirmed this divide—finding that community members’ evaluations of deadly force incidents are impacted by the race of the subject and by the precipitating event. Policy and research implications are presented.